Analisis Potensi Bahaya dan Evaluasi Risiko Menggunakan Job Safety Analysis (JSA) untuk Meningkatkan Keselamatan Kerja di PT Titilas Sembada Primandiri - Atthariq, Muhammad Adam Kemal; Kusnadi, Kusnadi; Nugraha, Asep Erik (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2025)
Work accidents are still common in the manufacturing sector despite various preventive measures that have been implemented. PT Titilas Sembada Primandiri, a company that manufactures electrical panels, faces high risks due to the complexity of the assembly process and the use of voltage equipment. This condition demands an in-depth analysis to identify hazards and assess the level of risk. This research aims to identify potential hazards, assess work risks, and provide control recommendations through the implementation of Job Safety Analysis (JSA) to improve occupational safety at PT Titilas Sembada Primandiri. A qualitative approach is used with direct observation in the work area and the application of JSA at each stage of electrical panel assembly to recognize hazards and determine control measures. The main hazards were found to be electric shock, physical injury, and equipment damage. The use of PPE, safety training, and strict implementation of SOPs are recommended to reduce the risk. JSA is effective in identifying and reducing the risk of work accidents in manufacturing environments. The research strengthens JSA as a proactive risk management tool in the industrial sector. Provide guidelines for companies in improving the culture of occupational safety.